Pengaruh Komunikasi, Lingkungan Kerja Dan Kepuasan Kerja Terhadap Organizational Citizenship Behavior (OCB) Pada Diva Swalayan Kraksaan Kabupaten Probolinggo - Tsurayya Ningsih; Muhammad Syarif Hidayatullah Elmas; Yekti Rahajeng (JUMAD : Journal Management, Accounting, & Digital Business, 2024)
The purpose of study is to determine the effect of the variables communication, work envronment and job satisfation on Organizational Citizenship Behavior (OCB) partially in Diva Swalayan Kraksaan, Probolinggo Regncy. This type of reseach use quantiative reseach methods, with a total samplle of 60 respondets who are employees of Diva Swalayan Kraksaan. Probability Sampling is the sample determination method, and Simple Random Sampling is the technique. Validity test, reliabilty test, clasical assumtion test, multipel liinear regresion analyss, the coeficient of deterination (R2) and also the T test are the data analysis methods. The resuts of the T test it is known that here is a positiv and signficant influece of tha variable of communication, work environment, and job satisfaction on Organizational Citizenship Behavior (OCB) of Diva Swalayan Kraksaan.